The Influence of Principal Leadership and Principal Management on Teacher Performance at the Babussalam Islamic Boarding School in Pekanbaru - Sahira, Mutia; Copriady, Jimmi; Hambali, Hambali (Journal of English Language and Education, 2025)
This study aims to analyze the influence of principal leadership and principal management on teacher performance at the Babussalam Islamic Boarding School in Pekanbaru. The research approach used is quantitative with a survey method through the distribution of questionnaires to 33 teachers as respondents. The results of the study indicate that principal leadership has a positive and significant effect on teacher performance. Similarly, principal management has a positive and significant effect on teacher performance. Simultaneously, both variables contribute significantly to improving teacher performance. These findings confirm that effective leadership and planned management can create a conducive working climate, increase motivation, and enhance the professionalism of teachers in the pesantren environment. Therefore, strengthening the role of the principal as an educational leader and manager needs to be continuously developed to support the improvement of education quality in Islamic boarding schools.